MAIN PROBLEMS OF PROVIDING PSYCHOLOGICAL SERVICE TO THE FAMILY - Akramova, F.A. (ILIM hám JÁMIYET, 2020)
When providing psychological assistance to families, knowledge and skills about the family are necessary. The article substantiates the need for psychological counseling, taking into account the typology of families, the level of performance of functions in the family, socio-psychological and demographic characteristics of families, and presents the necessary recommendations.